Assistance for Islamic Boarding School Students in the Jogoroto District Jombang Through Entrepreneurship With Macrame Skills - Ani Setyo Dewi, Yuli; Miftahillah; Rosalina, Irene; Choirudin (CV. Edutechnium Indonesia, 2023)
The activity of making macrame bags was carried out through training and product marketing. This was done to increase the income of productive age students and to increase sales of macrame bags through social media in Mayangan Village, Jogoroto District, Jombang Regency. The method of assisting community service activities used the ABCD approach (Asset Based Community Development). The result of the activity of making macrame bags for alumni students of Islamic boarding schools in the Jogoroto sub-district was to increase the income of students who were of productive age and could increase sales of macrame bags on social media.